Pharmaceutical Storage Management and Its Impact on Medication Obsolescence: A Case Study of Nizam Farma Pharmacy in 2025 - Iqbal Julian; Lusiana Ariani; Revalin Changestu (Indonesian Journal of Administrative and Clinical Pharmacy, 2026)
This evaluative study investigates the pharmaceutical storage management system at Nizam Farma Pharmacy to determine its degree of adherence to the Indonesian Ministry of Health (MOH) Regulation No. 73 of 2016 and the associated technical guidelines. A descriptive quantitative observational design was employed, utilizing a comprehensive 23-variable checklist for direct-site auditing. In addition to observational data, a secondary analysis of the facility’s 2024 medication expiration logs was conducted to identify obsolescence profiles of the medications. The pharmacy attained a compliance index of 0.80, correlating to the "Very Good" qualitative benchmark. Despite this, critical systemic vulnerabilities were identified in four variables: the absence of dedicated vaccine storage, lack of backup power infrastructure (generator), inconsistent routine inspections, and failure to implement specialized labeling and physical distancing for LASA (Look Alike Sound Alike) medications. Analysis of expired stock revealed that solid dosage forms accounted for 72% of losses, with Prescription Drugs (Obat Keras) representing 55% of the total. Furthermore, 80% of the expired items were categorized as "Slow-Moving" inventory. While Nizam Farma exhibits high foundational compliance, the reliance on an alphabetical-first in, first out (FIFO) hybrid rather than a strict First Expired, First Out (FEFO) system, coupled with branding proliferation in vitamins and antibiotics, serves as the primary driver of obsolescence. The remediation of safety protocols and cold-chain resilience is imperative.